2019
DOI: 10.1002/joe.21986
|View full text |Cite
|
Sign up to set email alerts
|

The exit interview in Pakistan's IT and banking industries: Mere formality or catalyst for change?

Abstract: Human resource professionals have long used exit interviews to help track employee turnover trends. These conversations between departing employees and one or more company representatives, however, can also serve as a window onto opportunities to improve organizational policies and performance. A study of the experiences of a sampling of banking and information technology professionals in Karachi, Pakistan, highlighted the impact of such factors as mode and timing on the effectiveness of the exit interview pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, employees must be given adequate time to work on the change project. Considering change fatigue comes from the perception that too much change is taking place, organizations must prioritize their change initiatives and communicate to employees which changes are important and urgent and which ones are not (e.g., Aqil & Memon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, employees must be given adequate time to work on the change project. Considering change fatigue comes from the perception that too much change is taking place, organizations must prioritize their change initiatives and communicate to employees which changes are important and urgent and which ones are not (e.g., Aqil & Memon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Workers who are younger and/or have shorter organizational tenures report greater WIF, and this increases turnover intentions (Kraak et al, 2017). Overall, previous research has shown that being dissatisfied with work and family life leads to thoughts of quitting (Aqil & Memon, 2020). This turnover intention can be organizational or occupational, depending on the employee's decision to either leave the organization (current bank) voluntarily or to leave the occupation altogether (the banking profession).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Because of their smaller capital, they are unable to capitalize on market opportunities (e.g., stocking when prices are lower), and informal financing does not present their business transactions to formal loan providers such as banks in order to secure loans (Islam et al., 2019). Moreover, the limited networking of women entrepreneurs is another significant barrier that impacts business performance in the competitive market of Bangladesh (Aqil & Memon, 2020;Orser, 2020; Islam et al., 2019). As a result, many female entrepreneurial ventures face severe profit loss, and many are closed permanently in the initial stage (Chmura, 2020).…”
Section: Introductionmentioning
confidence: 99%